Unveiling arguments on national system reforms of marine protected areas by extractive marine users in three maritime countries - Takafumi Ohsawa (Frontiers in Marine Science)
All coastal states are expected to establish marine protected areas (MPAs) in line with international targets. For most, this will mean a radical increase in the amount of marine area protected in this way. In order to achieve effective MPAs, the opinions of stakeholders must be carefully considered. This article examines the views of marine extractive users (people engaged in fishery and mining industries) in three coastal countries, the United Kingdom, Canada, and New Zealand, using public comments submitted in response to recent proposals for new MPAs. Specifically, I focus on practically ideal size, duration, required information for regulation, burden of proof and post-designation monitoring of MPAs. Therefore, the gathered material was analyzed to capture views on four issues: 1) to what extents MPAs should target geographical and time scale?; 2) to what extents MPAs should conserve objects and regulate activities based on limited evidence?; 3) who should bear the burden of proof with respect to the environmental impact of regulated activities?; and 4) who and how monitoring and research on ecosystems should be done in MPAs? The study finds that some extractive users oppose the large geographic/temporal scales of MPAs especially when these are based on the application of the precautionary approach. Others accepted these but use them to argue that their own activities are environmentally insignificant. Further, the arguments of some extractive users in favor of their industrial use of MPAs are also considered. These views were commonly found across all three countries, indicating that users in countries committed to the MPA project hold views that challenge this commitment. These findings suggest that challenges to the achievement of MPA targets lie ahead but also suggest new avenues of research and potential solutions. The paper makes six proposals for adjusting the application of the precautionary approach and related targets and regulations. In all cases, my results reinforce the importance of dialogue with marine extractive users for effective MPA reforms at the national and international levels.